In vivo monitoring of cystic fibrosis-like lung disease in mice by volumetric computed tomography - Wielpütz, Mark Oliver; Eichinger, Monika; Zhou, Z.; Leotta, Karin; Hirtz, Stephanie; Bartling, Sönke; Semmler, Wolfhard; Kauczor, Hans-Ulrich; Puderbach, Michael; Mall, Marcus A. (The European respiratory journal, 2011)
The onset and spontaneous development of cystic fibrosis (CF) lung disease remain poorly understood. In the present study, we used volumetric computed tomography (VCT) as a new method for longitudinal in vivo monitoring of early lesions and disease progression in CF-like lung disease in β-epithelial Na+ channel (ENaC)-transgenic (TG) mice. - Using a VCT scanner prototype (80 kV, 50 mA·s, scan time 19 s and spatial resolution 200 μm), βENaC-TG mice and wild-type (WT) littermates were examined longitudinally at 10 time-points from neonatal to adult ages, and VCT images were assessed by qualitative and quantitative morphological parameters. - We demonstrate that VCT detected early-onset airway mucus obstruction, diffuse infiltrates, atelectasis and air trapping as characteristic abnormalities in βENaC-TG mice. Furthermore, we show that early tracheal mucus obstruction predicted mortality in βENaC-TG mice and that the density of lung parenchyma was significantly reduced at all time-points in βENaC-TG compared with WT mice (median±sem -558±8 HU in WT versus -686±16 HU in βENaC-TG at 6 weeks of age; p<0.005). - Our study demonstrates that VCT is a sensitive, noninvasive technique for early detection and longitudinal monitoring of morphological abnormalities of CF-like lung disease in mice, and may thus provide a useful tool for pre-clinical in vivo evaluation of novel treatment strategies for CF.